Structural monitoring with fiber optic technology - Measures, Raymond M. (Academic, 2001)
This book is the first to address the field of structurally integrated fiber optic sensors. Fiber optic sensors embedded within materials and systems are able to measure a variety of parameters (i.e. temperature, vibration, deformation, strain, etc.) that allows for real time non-destructive evaluation. Examples include the following: monitoring structural fatigue in aging aircraft or loads in bridge structures. In more advanced applications, fiber optic sensors control actuators that allow materials to adapt to their environment. This gives rise to the names, "smart," "intelligent," and/or "a